1990
DOI: 10.1039/p29900001627
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical approach to the vibrational analysis of the nitroenamine system

Abstract: A comparative ab initio and semi-empirical study of the vibrational spectra of a series of nitroenamines with intramolecular hydrogen-bonds has been performed. Although the semi-empirical MN DO/H calculations reproduce qualitatively some of the observed spectral properties, the v( NO,) frequencies are considerably overestimated. The minimal basis set STO-3G gives the correct order for the frequencies of the characteristic vibrations of the nitroenamine system, and reproduces many of the observed structural eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…In compounds 7 (s-trans,Z geometry), the coupling affects mainly ν a (NO 2 ) and to a lesser extent the enamine band; the ν(C᎐ ᎐ O) vibration, that shows a negligible effect, does not seem to be coupled to δ(N᎐H). The results of the ab initio 3-21G theoretical calculations 18 for compound 5 (R 1 = H) are in accordance with these observations and also indicate that, in the strongest coupled isomer A, the enamine mode can be described as the symmetric combination of the C᎐ ᎐ O, C᎐ ᎐ C and C(1)᎐N stretching motions, with contribution of the C(1)᎐H and the N᎐H bending modes. The frequency shift (∆ν Ϫ32 cm Ϫ1 in CDCl 3 ) of the enamine band of E-6 relative to the same band of E-5b can be attributed to the lack of the δ[C(1)᎐H] mode in the composition of the band in the former compound, though the electronic effects introduced by the methyl group may also contribute.…”
Section: Discussionsupporting
confidence: 81%
“…In compounds 7 (s-trans,Z geometry), the coupling affects mainly ν a (NO 2 ) and to a lesser extent the enamine band; the ν(C᎐ ᎐ O) vibration, that shows a negligible effect, does not seem to be coupled to δ(N᎐H). The results of the ab initio 3-21G theoretical calculations 18 for compound 5 (R 1 = H) are in accordance with these observations and also indicate that, in the strongest coupled isomer A, the enamine mode can be described as the symmetric combination of the C᎐ ᎐ O, C᎐ ᎐ C and C(1)᎐N stretching motions, with contribution of the C(1)᎐H and the N᎐H bending modes. The frequency shift (∆ν Ϫ32 cm Ϫ1 in CDCl 3 ) of the enamine band of E-6 relative to the same band of E-5b can be attributed to the lack of the δ[C(1)᎐H] mode in the composition of the band in the former compound, though the electronic effects introduced by the methyl group may also contribute.…”
Section: Discussionsupporting
confidence: 81%
“…the COPh substituent, via the C --C bond, as found for other push-pull alkenes. [20][21][22][23][24][25][26][27] The key factor controlling the Z/E ratio is the strength of inter-and intramolecular hydrogen bonds which depends on, among other factors, the polarity of the medium 28,29 (Table 2). Polar solvents (EtOH, DMSO, acetone) enhance sulfur or nitrogen participation in the ground-state polarization, favoring the resonance forms A and B (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…Push-pull substituents reduce the double bond character yielding dipolar species thus lowering the rotational barriers. As mentioned, substituted ethylenes have attracted both experimental [5][6][7][8][9] and theoretical interest [5,6,10]. Theoretical calculations on 3-aminoacrylonitrile, 2, showed that the trans isomer was about 2 kcal/mol higher in energy than the cis isomer [6].…”
Section: Introductionmentioning
confidence: 95%
“…Gate and coworkers reported the ratio of cis/trans 2-nitroethylenamine, 3, to be 68:32 by 1 H-NMR spectroscopy in (CD 3 ) 2 SO 3 [8], and the X-ray crystal structure of (cis)-3 has been reported by Evans and Gilardi [9]. Vibrational frequencies as well as IR and Raman intensities have been calculated for 2-nitroethylenamine, 3, using low-level ab initio methods [10]. The trans isomer of 3-aminoprop-2-en-l-ylium cation, 4, was found to be 3 kcal/mole more stable than the cis isomer and the rotational barrier was determined to be 11.2 kcal/mol based on Hartree-Fock calculations employing the 3-21G basis set [11].…”
Section: Introductionmentioning
confidence: 97%